New polynuclear 1,5-naphthyridine-silver(I) complexes as potential antimicrobial agents: the key role of the nature of donor coordinated to the metal center - Đurić, Sonja Ž.; Vojnovic, Sandra; Pavic, Aleksandar; Mojicevic, Marija; Wadepohl, Hubert; Savić, Nada D.; Popsavin, Mirjana; Nikodinovic-Runic, Jasmina; Djuran, Miloš I.; Glišić, Biljana Đ. (Journal of inorganic biochemistry, 2020)
New polynuclear silver(I) complexes with 1,5-naphthyridine (1,5-naph), [Ag(NO3)(1,5-naph)]n (Ag1), [Ag(CF3COO)(1,5-naph)]n (Ag2) and [Ag(CF3SO3)(1,5-naph)]n (Ag3) were synthesized by the reaction of the corresponding silver(I) salt and 1,5-naph in ethanol at room temperature. These complexes were characterized by NMR, IR and UV-Vis spectroscopy, while their crystal structures were determined by single-crystal X-ray diffraction analysis. In all these complexes, 1,5-naph acts as a bridging ligand between two Ag(I) ions, while the remaining coordination sites are occupied by oxygen atom(s) of the corresponding anion. The antimicrobial efficiency of these silver(I) complexes was evaluated against the broad panel of Gram-positive and Gram-negative bacteria and fungi. The complexes showed good to moderate antibacterial activity with the minimal inhibitory concentration (MIC) values being in the range 2.5-100μg/mL (6.5-333.3μM), while their antifungal activity against the investigated Candida spp. was significantly higher (MIC=0.78-6.25μg/mL; 2.6-20.8μM). Moreover, complexes Ag1 and Ag2 effectively inhibited C. albicans biofilms formation, while Ag1 was also shown to inhibit the formation of mixed C. albicans/Pseudomonas aeruginosa biofilms. Toxicological evaluations on zebrafish (Danio rerio) embryos revealed that all silver(I) complexes could be applied as antifungal agents, whereas Ag3 had the best therapeutic potential showing both the lowest MIC values against the tested Candida strains and the non-toxic in vivo response in the zebrafish embryos at these doses.
Available online 23 October 2019
Gesehen am 03.04.2020